The Influence of Employee Involvement on Innovative Work Behavior with Workforce Agility as a Mediator - Deno Hadiarti; Yunizar; Wa Ode Zusnita Muizu (Bandung: Prodi Manajemen FE Universitas Langlangbuana, 2026)
Innovative work behavior has become an essential requirement for public sector organizations in responding to increasingly dynamic workplace changes. However, at the Center for Competency Development of Bina Marga, employees' innovative work behavior has not developed optimally despite their participation in competency development programs. This condition is presumed to be associated with employee involvement and employees' ability to adapt to changes in the workplace. This study aims to examine the relationship between employee involvement and innovative work behavior through workforce agility as a mediating variable. The study employed a quantitative approach using descriptive and explanatory research methods. The research population consisted of 831 training program alumni from the Center for Competency Development of Bina Marga, with the sample selected using proportionate stratified random sampling. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that employee involvement is positively associated with workforce agility, workforce agility is positively associated with innovative work behavior, employee involvement is positively associated with innovative work behavior, and workforce agility significantly mediates the relationship between employee involvement and innovative work behavior. These findings suggest that fostering innovative work behavior is associated with strengthening employee involvement and workforce agility alongside competency development initiatives.